PENGENDALIAN KETERLAMBATAN PENGIRIMAN BARANG MENGGUNAKAN METODE FTA DAN FMEA - Dony Rizky Kusuma Wijaya; Yugowati Praharsi; Danis Maulana (Program Studi D4-Manajemen Bisnis, Jurusan Teknik Bangunan Kapal, Politeknik Perkapalan Negeri Surabaya, 2022)
Logistics Company in Sidoarjo has a mission to be a safe, fast, and responsible logistics service provider. However, the high rate of shipping delays indicated the need a control to minimize the number of shipping delays. This study aims to identify the factors that causing shipping delays using FTA method, followed bydetermining repair priorities using the FMEA. An assessment using FMEA produces an RPN, where improvement priority will be given to the cause of failure with the highest RPN for each type of failure. The results of the study identified 16 causes of failure in shipping delays. Causes of failure with priority improvements on shipping delays are lack of coordination between divisions with an total RPN of 89.1, volume of goods exceeding capacity with an total RPN of 161.2, and insufficient cross-island trucks with an total RPN of 74.6.